Christmas, consumption and materialism: discourse analysis of children’s Christmas letters - Luna Batinga, Georgiana; de Rezende Pinto, Marcelo; Pimenta Resende, Sara (Review of Business Management, 2017)
Purpose – This article reports the results of an empirical research that sought to understand the many meanings referring to Christmas that appear in letters written by children and sent to Santa Claus. It is based on the idea that, by means of a playful activity such as writing Christmas letters, children would be able to bring up a variety of issues referring to their daily lives. Design/methodology/approach – This research, which is of interpretative nature, made use of elements belonging to discourse analysis. Discourse analysis is a theoretical and methodological field linked to Linguistics, which studies language in movement, producing meaning since it is a social practice. Findings – The results point to discursive marks that suggest traces of materialism and secularism in the narratives and stories created by children concerning Christmas. Moreover, Santa Claus is directly associated with the date and stands out as an emblematic figure in children’s imagination. Originality/value – Reporting Christmas imagery and the creation of its meanings by children can help unveil essential issues, or at least point out “clues” referring to the degree of symbolism that is present in the various social and cultural manifestations of contemporary society